Telling network stories: researching migrants' changing social relations in places over time. (7th July 2020) - Ryan, Louise
Abstract: This article is situated at the nexus of migration research and qualitative social network analysis (SNA). While migration scholars often engage with networks simply as metaphors, I go further by examining how a thorough engagement with qualitative SNA can contribute to migration research in at least three key ways. First, exploring changing relational ties over time and across different places, including transnationally, I demonstrate that qualitative SNA offers new insights into how migrants make sense of these dynamic relationships. Second, following Dahinden (2016), I examine how using networks as a data collection method can help to unsettle the a priori ethnic lens in researching migration. Moreover, building on the pioneering work of network scholars such as Mische and White, I aim to make a methodological contribution by analysing how social networks are co‐constructed as stories and pictures in research encounters.